2022
DOI: 10.3390/molecules27175726
|View full text |Cite
|
Sign up to set email alerts
|

Modified Protein-Water Interactions in CHARMM36m for Thermodynamics and Kinetics of Proteins in Dilute and Crowded Solutions

Abstract: Proper balance between protein-protein and protein-water interactions is vital for atomistic molecular dynamics (MD) simulations of globular proteins as well as intrinsically disordered proteins (IDPs). The overestimation of protein-protein interactions tends to make IDPs more compact than those in experiments. Likewise, multiple proteins in crowded solutions are aggregated with each other too strongly. To optimize the balance, Lennard-Jones (LJ) interactions between protein and water are often increased about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…We also note that the accuracy of our CG model can be improved by parameter recalibration against experimental results if they are available, for example, critical points of the scaffold proteins (such as TDP-43) and circular dichroism spectra or SAXS profiles of ligand proteins (such as Hero proteins). Alternatively, all-atom simulations using different force fields with improved parameters and advanced sampling methods ,, can provide more direct information such as atomic-level residue–residue interactions and motions of ions and water molecules.…”
Section: Discussionmentioning
confidence: 99%
“…We also note that the accuracy of our CG model can be improved by parameter recalibration against experimental results if they are available, for example, critical points of the scaffold proteins (such as TDP-43) and circular dichroism spectra or SAXS profiles of ligand proteins (such as Hero proteins). Alternatively, all-atom simulations using different force fields with improved parameters and advanced sampling methods ,, can provide more direct information such as atomic-level residue–residue interactions and motions of ions and water molecules.…”
Section: Discussionmentioning
confidence: 99%
“…HB1 is formed between the main chain amide N atom of Asp3 (hydrogen bond donor) and the main chain carbonyl O atom of Thr8 (acceptor). HB2 is an alternative to HB1 formed between Asp3:N and Gly7:O. HB1 and HB2 are considered good indicators to distinguish the native (HB1) and misfolded (HB2) states. , HB3 (Gly7:N–Asp3:O) is predominantly formed before HB1 and HB2 are formed . The trajectories in 3D space spanned by the distances of HB1, HB2, and HB3 were clustered into 2000.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Sugita and colleagues 45 demonstrated that, in the case of CHARMM36m, the scaling of the LJ parameter beyond a modest 3% increase of the protein-TIP3P water model interaction, while improving on protein−protein stickiness, can lead to protein instability. The study demonstrated that this small increase was sufficient to decrease protein stickiness occurring in a homogeneous villin (35 amino-acid residue protein) crowded model environment.…”
Section: ■ Methodsmentioning
confidence: 99%